FEATURES OF LONG-TERM OPERATION OF SPORTS FACILITIES (Physical Culture and Sport: Scientific Perspective, 2025)
The article discusses issues related to the study of the features of the operation of sports facilities. The great importance of sports facilities for society is emphasized. Sports facilities play an important social role, have an educational, cultural, social and educational function, have a great economic role and infrastructural value.Among the main issues that are in the focus of attention of scientists are the economic feasibility of sports facilities, adaptability for people with limited functional capabilities, various forms of joint maintenance, in particular cooperative forms, compliance with safety standards and regulations during training sessions. The unresolved issues are the uneven distribution of sports facilities across the country, insufficient consideration of the specifics of sports practiced in local communities, superficial study of citizens' interests and preferences regarding types of physical activity, and insufficient research into the level of physical fitness and sportsmanship of athletes.A study of the condition of sports facilities with a long service life allows us to point out the most problematic issues related to heating the facility in the cold season, wear and tear of the coating, deterioration of the drainage and water supply system, outdated and energy-consuming lighting systems, etc. An important condition for extending the life and quality of a sports facility is a comprehensive approach during repair and reconstruction. In order to rationally distribute financial costs, repair work should be carried out according to a long-term plan. The construction of modern sports facilities and the maintenance of sports facilities with a long service life require compliance with safe operating conditions, the arrangement of shelters.To improve the system of maintaining sports facilities, it is extremely important to take into account progressive foreign experience. Of greatest interest are the features of using modern and environmentally friendly materials in the construction of sports facilities, the use of energy-saving technologies for the maintenance of sports facilities, the study of the possibilities of transformation and redevelopment of the facility for holding various types of sports, and for organizing and holding mass sports events.